On certain exact relations for sojourn probabilities of a wiener process - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
New exact relations are proved for the sojourn probability of a Wiener process between two time-de-pendent boundaries. The proof is based on the investigation of the heat-conduction equation in the domain determined by these functions-boundaries. The relations are given in the form of series.